Greece : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2008)
The Greek economy showed strength supported by solid gains in employment, substantial real wage increases, low interest rates, and rapid credit expansion. Executive Directors appreciated the performance of the banking system and welcomed the Bank of Greece's efforts to strengthen provisioning requirements and lending standards. Directors welcomed the balanced budget and product market reform and stressed the need to improve tax administration. They advised that sustained fiscal consolidation is helpful for safeguarding debt sustainability. Directors emphasized for a budget framework to guide fiscal strategy and prioritize policy objectives.